Ripening induction of 'Packham's Triumph' pears treated wih 1-Methylcyclopropene (1-MCP) - Candan, Ana Paula; Calvo, Gabriela (ISHS, 2025)
Trabajo presentado al XI International Pear Symposium, Argentina, 2010